Improved melanoma outcomes and survival in patients monitored by total body photography: A natural experiment. Issue 4 (17th January 2020) - Strunck, Jennifer L.; Smart, Tristan C.; Boucher, Kenneth M.; Secrest, Aaron M.; Grossman, Douglas
Abstract: Total body photography (TBP) facilitates early melanoma detection, but long‐term outcomes have not been well studied. Our objectives were to examine melanoma diagnoses, role of TBP‐associated follow‐up visits, and survival in patients monitored by TBP. A total of 1955 patients meeting inclusion criteria received TBP from 2004–2013 at a single academic center. We compared the melanoma diagnoses and overall survival of 1253 patients with any follow‐up visits (median, three visits; range, 1–18) and 702 patients with no follow‐up visits. Use of TBP photographs influenced decision to biopsy 66 of 121 (54.5%) melanomas diagnosed after TBP. Lower invasive melanoma Breslow depth was significantly associated with having one or more follow‐up visit (median, 0.83 vs 0.33 mm; P  = .002) and photographic review (median, 0.31 vs 0.48 mm; P  = 0.02). In multivariable analyses, greater overall survival was significantly associated with having one or more follow‐up visit after TBP (hazard ratio [HR], 0.36; 95% confidence interval [CI], 0.14–0.91; P  < 0.032) and having more than 100 nevi (HR, 0.37; 95% CI, 0.22–0.64; P  = 0.004). Worse overall survival was significantly associated with increasing age (HR per year, 1.06; 95% CI, 1.04–1.08; P  < 0.001) and male sex (HR, 2.65; 95% CI, 1.48–4.73; P  = 0.001). Thus, monitoring by TBP was associated with subsequent melanoma diagnoses of lower stage and depth and greater overall survival.